Field Work Practice Monitoring System to Support Practical Activities for Vocational High School Students - Suparyati, Atik; Widiastuti, Indah; Saputro, Ida Nugroho (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Negeri Jakarta, 2024)
Internship (INTERNSHIP) is an important part of the vocational education curriculum in vocational high schools, including SMK Negeri 1 Gesi. However, its implementation often faces various obstacles, such as inefficient communication, delayed reporting, and difficulties in monitoring student progress. To address these issues, an Internship monitoring system has been developed with the aim of optimizing the learning process. Therefore, this research aims to develop a internship monitoring system that is suitable for use by vocational high school students to support their activities. The research method applied in this study is research and development adopting the Alessi & Trollip model. The research subjects include software/media experts, content experts, and teachers. Data collection is carried out using observation, interviews, and questionnaires. The data obtained from the research is then analyzed qualitatively descriptively and quantitatively in terms of percentage. The research results show that in the alpha testing phase, the internship monitoring system product received a High Validity qualification from experts. Based on these results, it can be concluded that the internship monitoring system product deserves the category of high feasibility to use as an application or system to support a series of internship activities, both for teachers and students.